150k views
5 votes
The solution for 7(5x+9)=12-(x+9) and simplified​

1 Answer

5 votes

Answer:

x= -5/3

Explanation:

Step 1: Simplify both sides of the equation.

7(5x+9)=12−(x+9)

7(5x+9)=12+−1(x+9)(Distribute the Negative Sign)

7(5x+9)=12+−1x+(−1)(9)

7(5x+9)=12+−x+−9

(7)(5x)+(7)(9)=12+−x+−9(Distribute)

35x+63=12+−x+−9

35x+63=(−x)+(12+−9)(Combine Like Terms)

35x+63=−x+3

35x+63=−x+3

Step 2: Add x to both sides.

35x+63+x=−x+3+x

36x+63=3

Step 3: Subtract 63 from both sides.

36x+63−63=3−63

36x=−60

Step 4: Divide both sides by 36.

36x/36 and -60/36

x= -5/3

User Vijay Boyapati
by
6.0k points